1971
DOI: 10.1029/rs006i002p00139
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic Crochets and Associated Ionospheric Current Systems

Abstract: It is shown that time‐structure analysis of geomagnetic crochets can be useful in the ground‐based detection of XUV radiation from solar flares. The crochets often manifest a composite structure that consists of a ‘fast’ component presumably produced by EUV radiation (100–1000Å) and a ‘slow’ component produced by soft X rays (1–100Å). This composite structure is taken into account in the proposed method of analysis for crochet current systems. Some preliminary results are given from the simulation studies of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 93 publications
4
49
0
Order By: Relevance
“…A geomagnetic crochet often consists of two components (Richmond and Venkateswaran 1971); a "fast component" is presumably produced by a rapid increase in the EUV radiation and a "slow component", which peaks a few minutes after the fast component, corresponds to a slow increase in soft X rays. Although the conductivity enhancement during solar flares is limited to the dayside ionosphere, several authors found evidence of solar flare effects during the nighttime (Ohshio et al 1963;Sastri 1975;Sastri and Murthy 1975).…”
Section: Storm Effectmentioning
confidence: 99%
“…A geomagnetic crochet often consists of two components (Richmond and Venkateswaran 1971); a "fast component" is presumably produced by a rapid increase in the EUV radiation and a "slow component", which peaks a few minutes after the fast component, corresponds to a slow increase in soft X rays. Although the conductivity enhancement during solar flares is limited to the dayside ionosphere, several authors found evidence of solar flare effects during the nighttime (Ohshio et al 1963;Sastri 1975;Sastri and Murthy 1975).…”
Section: Storm Effectmentioning
confidence: 99%
“…Ohshio et al (1967) studied sfe on geomagnetic field on global basis and suggested that the seat of ionospheric current due to solar flares is a little lower than the layer for Sq current system. Richmond and Venkateswaran (1971) suggested that the crochet consists of a 'fast' component presumably due to EUV radiation (100-1000Å) and a 'slow' component produced by soft X-rays (1-100Å). Forbush and Casaverde (1961) first took a proper attention to the crochet at equatorial electrojet region and showed that the enhancement of sfe in H at Peruvian stations varied in a manner similar to the enhancement of Sq (H ) itself.…”
Section: Introductionmentioning
confidence: 99%
“…An interpretation of SFE in terms of enhanced electrical conductivity due to solar X-ray flare flux enhancement in the band 1-20A was made by OHSHIO (1964) from a study of selected SFE events observed during I. G. Y. A recent study indicated that SFE is due to extra ionization produced by solar XUV (1-1000A) flare radiation and the SFE's often exhibit a composite structure consisting of a 'fast' component presumably due to EUV radiation (100-1000A) and a 'slow' component produced by soft X-rays (1-100A) (RICHMOND and VENKATESWARAN, 1971). A very recent study made by the authors using SFE's observed (on normal run magnetograms) at Kodaikanal (Lat: 10.20N;Long: 77.50E,Dip: 3.50N) showed that the amplitude of SFE is linearly correlated with peak solar X-ray flux level in the bands: 1-8A and 8-20A (monitored by SOLRAD-9) lending support to the interpretation that SFE is due to enhanced ionization produced by solar soft X-rays (SASTRI and MURTHY, 1975).…”
Section: Introductionmentioning
confidence: 99%